2000
DOI: 10.1074/jbc.m001705200
|View full text |Cite
|
Sign up to set email alerts
|

A 54-kDa Fragment of the Poly(A)-specific Ribonuclease Is an Oligomeric, Processive, and Cap-interacting Poly(A)-specific 3′ Exonuclease

Abstract: We have previously identified a HeLa cell 3 exonuclease specific for degrading poly(A) tails of mRNAs. Here we report on the purification and identification of a calf thymus 54-kDa polypeptide associated with a similar 3 exonuclease activity. The 54-kDa polypeptide was shown to be a fragment of the poly(A)-specific ribonuclease 74-kDa polypeptide. The native molecular mass of the nuclease activity was estimated to be 180 -220 kDa. Protein/protein cross-linking revealed an oligomeric structure, most likely cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
126
1
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(139 citation statements)
references
References 39 publications
(52 reference statements)
6
126
1
3
Order By: Relevance
“…4) and with longer substrates (COX17 50Nϩ10A) or the 366-nt MFA2-38A mRNA, there is clear pausing also immediately following deadenylation. This ability of mCAF1 to also processively degrade non-poly(A) sequences makes mCAF1 unique among the four known eukaryotic deadenylases, CAF1, CCR4, PARN, and PAN2 (10,14,22,27,28). yCAF1 has also shown to act distributively with poly(U) and poly(C) substrates (19).…”
Section: Table Imentioning
confidence: 99%
“…4) and with longer substrates (COX17 50Nϩ10A) or the 366-nt MFA2-38A mRNA, there is clear pausing also immediately following deadenylation. This ability of mCAF1 to also processively degrade non-poly(A) sequences makes mCAF1 unique among the four known eukaryotic deadenylases, CAF1, CCR4, PARN, and PAN2 (10,14,22,27,28). yCAF1 has also shown to act distributively with poly(U) and poly(C) substrates (19).…”
Section: Table Imentioning
confidence: 99%
“…PARN has been cloned from human and Xenopus laevis, and the PARN polypeptide is M r 74,000 in both cases (2,9). However, the active mammalian enzyme is significantly larger due to its oligomeric structure and most likely consists of three identical subunits (3).…”
Section: Poly(a)-specific Ribonuclease (Parn)mentioning
confidence: 99%
“…1 is the only mammalian poly(A)-specific 3Ј-exoribonuclease identified and characterized thus far (1)(2)(3)(4)(5). It has been shown that PARN is an oligomeric, highly processive, and mRNA cap-interacting exonuclease (3, 6 -8).…”
Section: Poly(a)-specific Ribonuclease (Parn)mentioning
confidence: 99%
“…A poly(A)-specific ribonuclease has been purified from calf thymus (8) and has very similar enzymatic properties to the activity in HeLa cells (9). In yeast there are two deadenylase complexes, Pan2p/Pan3p (41,42) and Ccr4p/Pop2p/Notp (43).…”
Section: P38 Mapk Inhibits Are-directed Deadenylationmentioning
confidence: 99%
“…The default mRNA decay pathway in eukaryotes begins by shortening of the poly(A) tail (4 -7). A mammalian poly(A)-specific ribonuclease has been identified (8,9), and a human homologue of the major cytoplasmic deadenylase in yeast, Ccr4p, has been cloned (10). In mammalian cell extracts deadenylation is followed by decay of the mRNA body, which occurs mainly in the 3Ј 3 5Ј direction due to the action of a large exonuclease complex or exosome (11)(12)(13); the 5Ј cap structure of the mRNA then being removed by a scavenger activity (11).…”
mentioning
confidence: 99%